2000
DOI: 10.1063/1.1328096
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption study of nitrogen in N-implanted GaAs and epitaxially grown GaAs1−xNx layers

Abstract: Fourier-transform infrared absorption measurements have been carried out in the two-phonon region of GaAs. Implantation of the nitrogen isotopes N14 and N15, respectively, into bulk GaAs shows that a local vibrational mode at 471 cm−1 (14N) is due to isolated nitrogen. The band is also found in GaAs1−xNx(0<x<0.03) layers grown by solid-source molecular beam epitaxy. The strength of the band correlates quantitatively with the decrease of the lattice parameter determined by x-ray diffraction for x&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20] Evidence for three different a Ќ ͑x͒ dependences can be found in the literature. Some authors have observed a linear behavior for x up to 0.05, 11 or even up to 0.10, 12 with a constant strain coefficient of ␣ V = −0.39.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20] Evidence for three different a Ќ ͑x͒ dependences can be found in the literature. Some authors have observed a linear behavior for x up to 0.05, 11 or even up to 0.10, 12 with a constant strain coefficient of ␣ V = −0.39.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown deviations from the linear dependence predicted by Vegard's rule above a certain critical N concentration, 0.01Ͻ x c Ͻ 0.03. Two types of deviations have been observed: negative 13,14 ͑␣ Ͻ ␣ V for x Ͼ x c ͒ with a minimum strain coefficient of −0.52; and positive [15][16][17][18][19][20] ͑␣ Ͼ ␣ V for x Ͼ x c ͒ with maximum strain coefficients between −0.3 and −0.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The issue of local bonding of nitrogen in these dilute alloys has so far been addressed for GaAsN and GaInAsN. Both infrared absorption 9 and Raman spectroscopy 10-12 revealed a vibrational mode near 470 cm Ϫ1 in dilute GaAsN, which is assigned to the vibration of nitrogen bonded to four Ga neighbors. 9 For GaInAsN, the same experimental techniques gave evidence for the presence of additional modes at slightly lower and higher frequency, which gain in strength upon, or even appear only after postgrowth thermal annealing.…”
Section: Preferential Formation Of Alan Bonds In Low N-content Algaasnmentioning
confidence: 99%
“…We find that the mode weight on the N atom is 94.6%, and the mode weight on the surrounding Ga atoms is 5.1%, meaning that the weight on the rest of the surrounding atoms is negligible. Single N substitution on an As site in GaAs results in a LVM at [57], which has been modeled accurately, resulting in a LVM frequency of 465 cm −1 [63,66], using a similar theoretical approach to the one we employ in the present work. Substitution of As by C in GaAs has been experimentally determined to result in a LVM at 582 cm −1 [113], which decreases by 42 cm −1 to 540 cm −1 for the case of C in GaSb [114].…”
Section: Localized Vibrational Modesmentioning
confidence: 99%